Descriptive¬¬–Interpretative Evaluation of SIMONEVA Palu Usability and User Experience Using Cognitive Walkthrough (CW) and User Experience Questionnaire (UEQ) - Aisyah Syahskiah Sunandar; Deny Wiria Nugraha (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2026)
The Monitoring and Evaluation Information System (SIMONEVA) plays an important role in supporting regional development, but it often generates user complaints and has not been systematically evaluated. This research evaluates the usability and user experience of SIMONEVA Palu and analyzes the descriptive-interpretative relationship between the severity of usability issues and user experience scores. The usability evaluation was conducted using the Cognitive Walkthrough (CW) method, involving 10 respondents, consisting of 5 long-term users and 5 new users, while the user experience measurement used the User Experience Questionnaire (UEQ) with 41 long-term users. The results of the descriptive-interpretative relationship analysis indicate that Attractiveness and Efficiency have critical usability issues (severity level = 4) with very low UEQ scores (0.04 and 0.20), while Dependability and Perspicuity have moderate issues (severity levels = 2.22 and 2.38) with low UEQ scores (0.09 and 0.12). The pattern found indicates that the higher the severity level of usability issues, the more negative the users' perception of the system. These findings emphasize that system evaluation needs to consider both operational barriers and users' subjective perceptions. Thus, the resulting recommendations are able to highlight interface areas that require improvement more specifically. This research is expected to contribute to the literature on government information system evaluation, particularly at the regional implementation level, which is still relatively limited.